2020
DOI: 10.1002/bse.2617
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the risks of adopting circular economy initiatives in manufacturing supply chains

Abstract: The concept of circular economy (CE) has proven its worth due to the scarcity of natural resources and huge amounts of wastage which impacts the environment. Thus, the adoption of the CE concept in the supply chain becomes critical. However, due to the complex nature of processes/activities in the circular supply chain (CSC), managing risk has become a priority to avoid disruption. In current literature, no discussion has been conducted on how to analyse the risks in the context of CSC. Therefore, to fill this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 146 publications
(102 reference statements)
0
60
0
Order By: Relevance
“…Tandon, 2020;Waker, de Alencar Nääs, Duarte, & Papalardo, 2018).Trust refers to users' expectation that logistics service provider behaves ethically, dependably and fulfill their expected commitments (Iassinovskaia, Limbourg, & Riane, 2017;Menidjel, Benhabib, Bilgihan, Madanoglu, & Management, 2019;Vuong & Khanh Giao, 2020). Commitment refers to a desire to maintain valuable relationship and the belief that it is important enough to make the utmost effort to maintain a lasting relationship with the exchange partner (Agag, 2019;Ertz, Durif, Lecompte, & Boivin, 2018;Ethirajan et al, 2021;Y. Li, Guo, & Zhang, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Tandon, 2020;Waker, de Alencar Nääs, Duarte, & Papalardo, 2018).Trust refers to users' expectation that logistics service provider behaves ethically, dependably and fulfill their expected commitments (Iassinovskaia, Limbourg, & Riane, 2017;Menidjel, Benhabib, Bilgihan, Madanoglu, & Management, 2019;Vuong & Khanh Giao, 2020). Commitment refers to a desire to maintain valuable relationship and the belief that it is important enough to make the utmost effort to maintain a lasting relationship with the exchange partner (Agag, 2019;Ertz, Durif, Lecompte, & Boivin, 2018;Ethirajan et al, 2021;Y. Li, Guo, & Zhang, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although they have studied these barriers precisely, they have ignored some barriers, such as organizational and financial barriers. Another study conducted by Ethirajan et al (2021) placed emphasis on the risks and threats pertaining to CE affairs in the supply chain of manufacturing companies. They reported the availability of 31 risks in this area and employed DEMATEL approach to assess these risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They suggested that in the future, the framework could be refined by considering a greater sample size. CE is considered as an alternative to the traditional approach of ‘make–use–dispose’ (Ethirajan et al, 2020). In the manufacturing sector, many organisations are striving hard to position themselves better, but appropriate strategies have not been identified for them in existing literature for CE implementation.…”
Section: Previous Literaturementioning
confidence: 99%
“…In‐depth interviews could also be conducted to obtain quantitative data. Ethirajan et al (2020) analysed risks associated with CE initiatives in the SC of a manufacturing organisation. Their study found 31 risks associated with CE initiatives and used a DEMATEL approach to analyse identified risks.…”
Section: Previous Literaturementioning
confidence: 99%